STUDI ETNOFARMASI TANAMAN OBAT TRADISIONAL PADA MASYARAKAT DI KECAMATAN PENRANG, KABUPATEN WAJO, PROVINSI SULAWESI SELATAN - Virsa Handayani; Andi Amaliah Dahlia; Andi Fenny Nurvadillah (Fakultas Farmasi UMI, 2022)
Indonesian community have been utillsing medicinal plants for years as an alternative treatment of a disease. Penrang is one of the areas located in Wajo Regency, South Sulawesi Province whre the majority is Buginese tribe. They use plants as a traditional medicine to cure various diseases. This research aimed to find out the types of plants used by local people in treating plants through shamans, community leaders and people who have knowledge about medicinal plants. The research method was purposive sampling. The research included 33 families and 54 species of ethnopharmacy still remains in the community to treat disesases that are used single-use or concoction, called jappi-jappi